The Laplacian-Energy-Like Invariants of Three Types of Lattices - Zheng-Qing Chu; Jia-Bao Liu; Xiao-Xin Li (Journal of Analytical Methods in Chemistry)
This paper mainly studies the Laplacian-energy-like invariants of the modified hexagonal lattice, modified Union Jack lattice, and honeycomb lattice. By utilizing the tensor product of matrices and the diagonalization of block circulant matrices, we derive closed-form formulas expressing the Laplacian-energy-like invariants of these lattices. In addition, we obtain explicit asymptotic values of these invariants with software-aided computations of some integrals.